Educación sexual en los/as estudiantes adolescentes de la Unidad Educativa “José Rodríguez la Bandera” de la parroquia los Guayacanes del cantón Quevedo provincia de Los Ríos, en el primer quimestre del período lectivo 2013 – 2014 - Delgado Peña, Narcisa Pilar (2013)
Since adolescents admitted to a Middle Level Education campus, you must transmit values of sexuality which will assume a leading role in society, within the framework of a healthy coexistence with the principals, teachers, peers and the school community. Sex education in the (as) students “Jose Rodriguez Labandera” Education Unit of the Parish the Quevedo Canton Guayacanes Rivers Province in the first Quimestre the 2013-2014 period. The educational institution has no medical department, which presents a lack of knowledge about sexuality which evidenced the problems as sexually transmitted diseases, teen pregnancy, low academic performance, Social Problems. In order to determine the impact of sex education on adolescent students, as well as determine the level of knowledge about sex education, this research proposes nursing interventions on sex education, new strategies used by nurses and teachers, determine the factors that facilitate or limit the teaching of sex education. As such, that may lead to healthy relationships in coexistence with their psychosocial environment. We conclude, by not having medical department, have no quality advice aimed at risk reduction activity that could make a nurse since 77.14% of the students have asked about (ITS) on the recommendation of their pedagogical teachers, while 22.86% of not knowing about it. Is recommended. Than the establishment must have medical department as indicated by the MOH health standards in Ecuador which indicates that for every 500 students there must be a team of health that will permit the reduction of risk of disease or pregnancy premature.